Pengembangan Media Pembelajaran Teknik Elektronika Dasar Kelas X Program Keahlian Teknik Audio Video Menggunakan Swishmax - Ilhamdi Ilhamdi; Yasdinul Huda (Kognitif: Jurnal Pendidikan dan Inovasi Pembelajaran, 2025)
This study aims to develop the media, determining  the performance of the media and the feasibility level of the learning media for Basic Electronics Engineering Class X Audio Video Engineering Expertise Program using Swishmax. This research is a Research and Development (R&D) research. The object of this research is learning media using Swishmax. The product manufacturing stage includes 1) Requirements analysis, 2) Reference collection, 3) Design, 4) Validation, 5) Revision, 6) Testing use. The data collection method used a questionnaire. The results showed that making learning media using Swishmax was adapted from Sugiyono’s research method. Getting material validation 91,56% and media validation gets 92,94% with a level of feasibility “Very Appropriate”. Meanwhile, the test of use by students also got 92,45% with  a level of feasibility “workable”.